PENGARUH ASAM FULVAT TERHADAP PERTUMBUHAN, PRODUKTIVITAS, DAN MUTU RIMPANG JAHE - MUHAMAD DJAZULI; IRENG DARWATI; ROSITA SMD (Jurnal Penelitian Tanaman Industri, 2001)
Fulvic acid is an extraction product of humus which is very potential for supplement fertilizer and able to reduce either inorganic or organic fertilizer application. The information about fulvic acid application as supplement fertilizer on ginger in Indonesia is still limited. The objective of the study was lo find oul the efect of fulvic acid as supplement fertilizer on the growth, productivity and quality of young ginger. A green house trial was conducted from July lo November 1996. Five levels of fulvic acid concentration, 0, 2.5, 5, 7.5, and 10% were sprayed every week from 4 to 1 5 weeks ater planting (WAP). A randomized block design was used with five replicates. The results indicated that the growth of plant height and number of tiller of ginger increased rapidly al 8 WAP, then il became slowly from 12 lo 1 5 WAP Application 10% of fulvic acid was able to increase vegetative parts 99.6%, fresh and dry weight of rhizome 89 and 125% respectively, and starch content of rhizome 22.6%. To find oul of the optimal effect of fulvic acid on productivity and quality of ginger, a further research using higher level and application frequency of fulvic acid as an extract product from several humus types in Indonesia is needed.